1992
DOI: 10.1149/1.2221163
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rapid Thermal Precleaning for Si Epitaxial Growth

Abstract: In this paper, in situ H., precleaning of bare and oxide patterned (1O0) Si substrates was studied at 800-1100~ and 5 Torr with base pressures of 1.5 x 1() -~ to 7 x 10 -~ Torr. The preclean can cause considerable surface damage due to enhanced etching, which strongly depends on process parameters such as base pressure and temperature. High preclean temperatures with low base pressures cause severe surface roughness, impacting subsequent film growth. Optimized preclean conditions produce damage-free surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Hydrogen desorption, if overdone, also leads to etching of the Si surface. 3,13,14 Thus, as will also be shown in this paper, sub-optimal desorption results in incomplete oxide removal and excessive desorption results in surface damage. This necessitates the use of an optimum time-temperature thermal desorption step, with or without ex-situ oxide removal.…”
mentioning
confidence: 52%
“…Hydrogen desorption, if overdone, also leads to etching of the Si surface. 3,13,14 Thus, as will also be shown in this paper, sub-optimal desorption results in incomplete oxide removal and excessive desorption results in surface damage. This necessitates the use of an optimum time-temperature thermal desorption step, with or without ex-situ oxide removal.…”
mentioning
confidence: 52%
“…surfaces with dangling bonds being mostly occupied by H or F atoms that are stable for a few tens of minutes in ambient conditions, enabling sample transfer and loading. An H 2 -bake, typically between 800 C and 900 C for a few tens of seconds up to a few minutes [11,[21][22][23][24][25][26], will lead to the removal of any C, O or F residual atoms and to the formation of smooth [24,27] (2 Â 1):H reconstructed surfaces that are much more stable in the air [28] (up to 40 h [29]).…”
Section: Surface Preparationmentioning
confidence: 99%
“…Several groups have tried to minimize the thermal budget necessary for the H 2 bake [21,25,26,30]. What has been found on fullsheet wafers is that an optimized wet clean [last step: 1:1000 HF(49%):deionized water] followed by an H 2 bake at 800 C for 2 min is sufficient at 10 Torrs to produce oxygen and carbon-free Si surfaces [26].…”
Section: Surface Preparationmentioning
confidence: 99%
“…The conventional method of desorbing the native oxide from the silicon surface by a high temperature (>1000ЊC) anneal is incompatible with ULSI. 8 These concerns have resulted in the development of a cleaning process which removes the native oxide in a dilute HF etch, leaving the surface passivated with hydrogen. Hydrogen desorbs at lower temperatures (ϳ400ЊC) which is compatible with low thermal budget requirements of ULSI.…”
mentioning
confidence: 99%
“…15 Using a rapid thermal (RT) CVD reactor, Hsieh et al demonstrated that good quality epitaxial films were deposited by a surface preparation method that consists of a dilute HF dip and DI water rinse followed by hydrogen bake for 60 s at 800ЊC. 8 In 1995, using an ultrahigh vacuum rapid thermal CVD system and a similar ex situ clean, Sanganeria et al showed that interfacial carbon and oxygen could be reduced below the secondary ion mass spectroscopy (SIMS) detection levels by an in situ clean at 800ЊC/10 s in an ambient free of any chlorinated residuals. 16 In an earlier publication, we studied this surface preparation method in a chlorinated ambient for selective silicon epitaxial growth and demonstrated that a vacuum anneal at 800ЊC for 10 s was sufficient to reduce the oxygen and chlorine on Si(100) below the SIMS detection levels and significantly reduce the interfacial carbon.…”
mentioning
confidence: 99%